Variation in Negation Patterns of Verbless Clauses in Ammani Arabic - Hamdieh, Aya Mohammad; Jarrah, Marwan; Altakhaineh, Abdel Rahman Mitib; Al-shawashreh, Ekab (Jordan Journal of Modern Languages & Literatures, 2022)
This study aims to examine the extent to which the alternation between the common negation patterns of verbless clauses in Ammani Arabic, namely [mu] and [miʃ], is socially constrained. Gender, age, level of education and region (West Amman vs. East Amman) were investigated in this regard. Twenty-five hours of audio-recorded sociolinguistic interviews with 32 speakers who were born and raised in Amman were conducted. After using computer software GOLDVARB X (Sankoff et al. 2005), we propose that the alternation between [mu] and [miʃ] is socially conditioned. The most significant social factor is gender. The variant [mu] is found to be a solid sign of femininity. The second most significant social factor is age, whose effect is correlated with the assumption that young speakers, unlike old speakers, prefer less-complex forms. Education and region were also found, yet to a lesser extent, significant. West Amman speakers prefer [miʃ] in contrast to East Amman people who prefer [mu]. Although this finding is arguably unpredicted as [mu] is the variant which is socially viewed as more prestigious (therefore it would be more preferred by wealthier West Amman dwellers), it is nonetheless consistent with the demographic situation of Amman. East Amman is mostly inhabited by Jordanians who descended from Palestinian regions of which the common negation pattern of verbless sentences manifests [mu] rather than [miʃ]. Keywords: Language Variation and Change, Verbless-Sentences Negation, Age, Gender, Education, Region, Ammani Arabic.